Mens Sana in Corpore Sano! The Hiring Premium for Physical versus Mental Exercise in Different Occupations - Dieter Verhaest; Stijn Baert (Institute of Labor Economics (IZA), 2023)
We investigate the impact of participation in physical and mental exercise activities on hirability. Besides by comparing both forms of exercising, we innovate against the existing literature by comparing their impact between different types of jobs, where other effects could be expected. To this end, an audit experiment is conducted in which we send 2184 fictitious applications of young job seekers to real job vacancies. On average, the estimated effect of both physical and mental exercise activities is small and statistically insignificant. However, the effect of participation in any exercise activity is significantly positive for jobs combining low cognitive with low physical demands. These findings are not consistent with the common consideration of physical exercise activities being used by employers as signals of physical fitness and appearance.
Keywords: J24; J63; 330; sports; mental fitness; skills; employment; field experiments